2020
DOI: 10.7759/cureus.9627
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Gallbladder Histopathology at a Tertiary Hospital in a Developing Country: A Retrospective Study

Abstract: Background Affections of the gallbladder remain exceedingly ubiquitous and often warrant surgical intervention. The histopathological patterns represent a spectrum, ranging from cholecystitis to gallbladder carcinoma. The present study aims to delineate the occurrence of various gallbladder histopathologies in a tertiary care hospital in Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…15 In the present study, the age of the patients ranged from 12 years to 78 years and average age of presentation was 43.13 years, whereas for malignant lesions it was 53 years. Maximum cases who underwent cholecystectomy for gallbladder diseases were seen in 4 th and 5 th decades of life (Table1), which was similar to study by Almas T et al 13 and Beena D et al 16 In the present study calculi were retrieved in only 348 cholecystectomy specimens out of the total 760 cases examined. In these 348 cases, mixed cholesterol/pure cholesterol stones were more common and seen in 87.36% of cases, whereas pigment stones were seen in 12.64% of cases (fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…15 In the present study, the age of the patients ranged from 12 years to 78 years and average age of presentation was 43.13 years, whereas for malignant lesions it was 53 years. Maximum cases who underwent cholecystectomy for gallbladder diseases were seen in 4 th and 5 th decades of life (Table1), which was similar to study by Almas T et al 13 and Beena D et al 16 In the present study calculi were retrieved in only 348 cholecystectomy specimens out of the total 760 cases examined. In these 348 cases, mixed cholesterol/pure cholesterol stones were more common and seen in 87.36% of cases, whereas pigment stones were seen in 12.64% of cases (fig.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study out of total 760 cases, 595 cases were obtained from the females, with a female to male ratio of 3.6:1, which was comparable to study by Almas T et al and Mushtaq M et al 13,14 Increased estrogen levels in females increase cholesterol excretion in the bile leading to its supersaturation, and hence a 2-3 times higher risk of gallstones in reproductive aged females as compared to their male counterparts. In pregnancy gallbladder evacuation function also suffers which further increase the risk of gallstone diseases, especially in multiparous females.…”
Section: Discussionsupporting
confidence: 84%
“…This is in contrast to a study done in Pakistan, which found a greater percentage of 32.8% of people had this condition. 13 The histopathology revealed lipid laden macrophages along with villous hypertrophy causing yellowish streaks.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually 1 to 9% symptomatic adenomyomatosis; in these cases cholecystectomy is indicated. It presents with abdominal pain [ 14 ]. In this study, patients who presented had symptoms of chronic cholecystitis and after histopathology report revealed adenomyomatosis.…”
Section: Discussionmentioning
confidence: 99%